FISHING PRODUCTION OF Pinirampus pirinampu AND Brachyplatystoma platynemum CATFISH HAS BEEN AFFECTED BY LARGE DAMS OF THE MADEIRA RIVER (BRAZILIAN AMAZON) - Igor Rechetnicow Alves SANT'ANNA; Carlos Edwar de Carvalho FREITAS; Raniere Garcez Costa SOUSA; Hélio Daniel BELTRÃO dos Anjos; Carolina Rodrigues da Costa DORIA (Boletim do Instituto de Pesca)
The present work analyzed landing events of commercial fishing boats carrying two species of large catfish in 11 fishing landing sites along the Madeira River, temporally and spatially characterizing the exploitation of these species before and after the closure of the Jirau and Santo Antônio hydroelectric dams. Our results show that the Madeira River dams may be negatively impacting the fishing production of Pinirampus pirinampu and Brachyplatystoma platynemum catfish, drastically reducing these species’ biomass as well as the incomes of regional fishers. If the irreversible loss of these species of Amazonian catfish is to be avoided, public policies and measures for the management and sustainable handling of this fishery resource must be urgently carried out.